Mesenteric thrombosis in patient victim of blunt abdominal trauma - Collaço,Iwan Augusto (2008)
INTRODUCTION: Mesenteric thrombosis related to trauma is an uncommon entity and has poor prognosis when associated to low perfusion and hemorrhagic shock. Usually presents a challenging diagnosis and high mortality rates, despite appropriate treatment. OBJECTIVE: To relate a case of a car accident and blunt abdominal trauma with terminal ileum and right colon necrosis. CASE REPORT: After initial procedures, complementary exams showed ribs and humerus fractures. Computerized tomography evidenced aerial distension in small bowel, gastric stasis and hidro-pneumothorax. Hypotension was observed during clinical observation followed by cardiopulmonary arrest, responding to reanimation. At surgery, it was found extensive necrosis of right colon and terminal ileum, and an ileum-transversostomy was performed with primary anastomosis. During the staying in intensive care unit, oliguria, miosis, convulsion and pulseless electric activity happened with death in three days after hospital admission. CONCLUSION: Although uncommon, mesenteric ischemia with venous thrombosis might be secondary to blunt abdominal trauma and must be considered in a bad abdominal evolution.